Optimal management of patients with operable pancreatic head cancer: A Markov decision analysis. Issue 5 (7th July 2021) - Rieser, Caroline J.; Narayanan, Sowmya; Bahary, Nathan; Bartlett, David L.; Lee, Kenneth K.; Paniccia, Alessandro; Smith, Kenneth; Zureikat, Amer H.
Abstract: Introduction: Neoadjuvant therapy (NAT) is an emerging strategy for operable pancreatic ductal adenocarcinoma (PDAC). While NAT increases multimodal therapy completion, it risks functional decline and treatment dropout. We used decision analysis to determine optimal management of localized PDAC and consider risks faced by elderly patients. Methods: A Markov cohort decision analysis model evaluated treatment options for a 60‐year‐old patient with resectable PDAC: (1) upfront pancreaticoduodenectomy or (2) NAT. One‐way and probabilistic sensitivity analyses were performed. A subanalysis considered the scenario of a 75‐year‐old patient. Results: For the base case, NAT offered an incremental survival gain of 4.6 months compared with SF (overall survival: 26.3 vs. 21.7 months). In one‐way sensitivity analyses, findings were sensitive to recurrence‐free survival for NAT patients undergoing adjuvant, probability of completing NAT, and probability of being resectable at exploration after NAT. On probabilistic analysis, NAT was favored in a majority of trials (97%) with a median survival benefit of 5.1 months. In altering the base case for the 75‐year‐old scenario, NAT had a survival benefit of 3.8 months. Conclusions: This analysis demonstrates a significant benefit to NAT in patients with localized PDAC. This benefit persists even in the elderly cohort.